Cavanaugh in plain sight - Ferrarella, Marie (Ferrarella, Marie. Cavanaugh justice., 2020)
"Journalist Krys Kowalski doesn't shy away from uncovering scandal- even if it means putting her life in danger. When her latest investigation endangers her life, Krys enlists Detective Morgan Cavanaugh as a 24/7 bodyguard. But she won't give up, even as the attraction between her and Morgan simmers- even if the job costs her her life!" --Amazon.